2011
DOI: 10.1128/jcm.05122-11
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outbreak of Community- and Hospital-Acquired Mycobacterium porcinum Infections Related to Public Water Supplies

Abstract: Mycobacterium porcinum is a rarely encountered rapidly growing Mycobacterium (RGM). We identified M. porcinum from 24 patients at a Galveston university hospital (University of Texas Medical Branch) over a 5-year period. M. porcinum was considered a pathogen in 11 (46%) of 24 infected patients, including 4 patients with community-acquired disease. Retrospective patient data were collected, and water samples were cultured. Molecular analysis of water isolates, clustered clinical isolates, and 15 unrelated contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…Indeed, M. porcinum has mainly been reported in water supplies in tropical or subtropical areas in the USA (22,23), Iran (24), Brazil (25) and Mexico (26). We report M. porcinum isolates identified in three patients with M. porcinum lung infection according to the ATS criteria (13), which is consistent with other cases reported previously, particularly in subtropical areas such as Texas and Florida, where clonal dissemination was ob- served, particularly through water systems (22,27).…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, M. porcinum has mainly been reported in water supplies in tropical or subtropical areas in the USA (22,23), Iran (24), Brazil (25) and Mexico (26). We report M. porcinum isolates identified in three patients with M. porcinum lung infection according to the ATS criteria (13), which is consistent with other cases reported previously, particularly in subtropical areas such as Texas and Florida, where clonal dissemination was ob- served, particularly through water systems (22,27).…”
Section: Discussionsupporting
confidence: 79%
“…In a review of RGM bacteraemia,9 it was found that the use of at least two active antimicrobials for a minimum of 4 weeks, including the removal of any intravascular catheter, leads to resolution of infection in more than 90% of cases. Antimicrobial susceptibilities of M. cosmeticum is only documented in two other reports 1 3. Including our case, M. cosmeticum showed uniform susceptibilities to amikacin, ciprofloxacin, cefoxitin, clarithromycin, imipenem and trimethoprim/sulfamethoxazole.…”
Section: Discussionsupporting
confidence: 49%
“…This case also coincided with a sharp increase in M. porcinum isolates causing disease at the University of Texas Medical Branch in Galveston, Texas, USA, which was attributed to water contamination during Hurricane Ike 1. Although M. cosmeticum was not isolated from environmental cultures at the time, direct surface cultures from the equipment used during IBT were not collected and cannot be excluded as a source of infection.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Other species closely related to M. fortuitum were also isolated although not distinguished to the species level in most cases (i.e., M. phocaicum/mucogenicum, M. senegalense/houstonense/ conceptionense, M. peregrinum, and M. porcinum). These mycobacterial species have also been described as important facultative pathogens in humans (Brown-Elliott and Amorim et al, 2010;Brown-Elliott et al, 2011;Kim et al, 2012).…”
mentioning
confidence: 98%